Pre-Acting Control for Shock and Impact Isolation Systems. (2005) - Balandin, D.V.; Bolotnik, N.N.; Pilkey, W.D.
Abstract : Pre-acting control in shock/impact isolation systems is studied. With pre-acting control, the isolation system begins to respond to an impact before this impact has been applied to the base. The limiting performance of the isolator with pre-acting control is investigated for a single-degree-of-freedom system subject to an instantaneous impact. The isolation performance index is defined as the maximum of the absolute value of the displacement of the object to be isolated relative to the base, provided that the magnitude of the control force transmitted to the object does not exceed a prescribed value. It is shown that there is a substantial advantage in the use of pre-acting isolators over isolators without pre-action. Particular attention is given to a pre-acting isolator based on a passive elastic element (a spring) separating the object to be protected from the base. An example illustrates the calculation of the design parameters of such an isolator.